PEMBERIAN RESTITUSI TERHADAP KORBAN ATAU AHLI WARIS DALAM TINDAK PIDANA PERDAGANGAN ORANG - Boy Amali; Alvi Syahrin; Muhammad Ekaputra; Chairul Bariah (Universitas Sumatera Utara, 2018)
ABSTRACT Every victim of human trafficking crime or their heirs the right to obtain restitution. Restitution referred to in paragraph (1) for damages above: a. loss of wealth or income, b. suffering, c. costs for medical care actions and / or psychological and / or d. other losses suffered by the victim as a result of trafficking. The refund was given and included simultaneously in the ruling court on criminal case of human trafficking. Restitution carried out since the first level court decision handed down may be deposited in advance at the court where the case is disconnected. Restitution is done within 14 (fourteen) days from assured decision that has obtained permanent legal force. The perpetrator was acquitted by the court of appeal or cassation, the judge ordered restitution in the decision that the money deposited is returned to the person concerned. The conclusion of this thesis, 1.Government Indonesia is expected to soon establish minimum standards for the eradication of trafficking in persons. Furthermore, it should start using the Law No. 21 Year 2007 on Eradication of Trafficking in workers' trade practices. Improvement in the performance of the courts, prosecution and sentencing in cases of labor trafficking, including those involving labor recruitment agencies. Checking back in a Memorandum of Understanding with the countries that became the purpose of trading to incorporate protection of the victim. Need for increased efforts to prosecute and convict public officials who profit from or are involved in trafficking. Increase funding for law enforcement and rescue, restore and reintegrate victims. 2. Though no firmness in Law No. 21 of 2007 as mentioned above, wants to decisions restitution, executor of execution is the prosecutor, because since the beginning of the prosecutor has been involved in the filing restitution claims. (Article 50 paragraph (3) of Law No. 21 of 2007). If the merger of damages and criminal cases in the Criminal Code, implementing the execution of criminal decisions implemented by the Prosecutor (Article 270 Criminal Procedure Code), while the decision of restitution / compensation is carried out according to the procedures of the civil judgment (Article 274 of the Criminal Code) .3.Laws Number 21 Year 2007 to be immediately implemented by the issuance of Government Regulation (PP) on mechanisms and Procedures Restitution for Victims of Crime of Trafficking in Persons. In the PP least should regulate: a.Tata how to care restitution and the role of prosecutors in filing surrogate restitusi.b.Tata to calculate the value loss to be submitted to the court and the prosecution authorities determine the amount of losses that will be submitted to the court. c. Authority prosecutors filed the restitution is mandatory not voluntary so that he does not need approval from the victim, unless the victim asked the prosecutor not to file a restitution claim. d. Attitude prosecutor if the victim is more than one, there are welcoming the decision and some are wanting appeal. But should the prosecutor suggested to those who refuse to file a lawsuit through the civil order not to harm the victim receives. e.Must firmness that the execution must go through the prosecutor, so that prosecutors can actually carry out surveillance that restitution was met by the offender. Keywords: Restitution, Victims Or Heirs, Crime, Human Trafficking.